Risk and Ride: Understanding Safety and Security in Jakarta’s Motorcycle-based Ride-Sourcing - Anggun Dwi Ermawati; I Gusti Ayu Andani (Journal of Regional and City Planning, 2025)
The use of motorcycle-based ride-sourcing services for medium-distance travel as a feeder for home-based trips poses higher risk to passenger safety and security during the trip. This study aimed to identify the perception of safety and security of motorcycle-based ride-sourcing users and its influence on the preference for motorcycle-based ride-sourcing as a feeder mode for Jakarta’s metro system in home-based trips. The method used to determine user perception was principal component analysis (PCA) and the binomial logit model was estimated to analyze user preferences in choosing motorcycle-based ride-sourcing based on attributes such as travel time, cost, and safety and security features. The findings reveal that female respondents tend to choose motorcycle-based ride-sourcing more than male respondents; users traveling for mandatory trips are more likely to opt for motorcycle-based ride-sourcing; and the frequency of using motorcycle-based ride-sourcing to reach their residence as well as the perception of service management, significantly influence the choice of motorcycle-based ride-sourcing as a feeder mode for Jakarta’s metro system. However, individuals with a secondary education level tend to avoid using motorcycle-based ride-sourcing services. The model highlights that, in addition to travel time and cost, safety and security features, along with effective service management in motorcycle-based ride-sourcing, can increase the likelihood of their adoption as a feeder mode for the Jakarta’s metro system. Therefore, motorcycle-based ride-sourcing operators are advised to improve the service by developing these features to provide better safety and security for users.